2012
DOI: 10.1590/s1678-77572012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Xylitol concentrations in artificial saliva after application of different xylitol dental varnishes

Abstract: Objective The present study analyzed xylitol concentrations in artificial saliva over time after application of varnishes containing 10% and 20% xylitol. Material and Methods Fifteen bovine enamel specimens (8x4 mm) were randomly allocated to 3 groups (n=5/group), according to the type of varnish used: 10% xylitol, 20% xylitol and no xylitol (control). After varnish application (4 mg), specimens were immersed in vials containing 500 µL of artificial saliva. Saliva samples were collected in different times (1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
(46 reference statements)
1
6
0
1
Order By: Relevance
“…Furthermore, varnish is a professional product whose application does not depend on the daily patient's compliance, which could favour its effect. Pereira et al 27 found significant higher xylitol concentrations released in saliva after application of a 20% xylitol varnish compared to a 10% xylitol varnish on a short-term basis (up to 8 h). This result is clinically relevant, since dental varnishes are usually removed from tooth surfaces after 6 to 12 h of application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, varnish is a professional product whose application does not depend on the daily patient's compliance, which could favour its effect. Pereira et al 27 found significant higher xylitol concentrations released in saliva after application of a 20% xylitol varnish compared to a 10% xylitol varnish on a short-term basis (up to 8 h). This result is clinically relevant, since dental varnishes are usually removed from tooth surfaces after 6 to 12 h of application.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Xylitolcontaining varnishes have been recently developed. They were shown to be effective to increase salivary xylitol levels 27 and to reduce erosion. 21 However, their effect in the remineralization of caries lesions has never been evaluated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives of these sugars have been reported as important materials for industrial application (Krogell et al, 2013;Zhou et al, 2013). For example, xylitol that produced from hydrogenation of xylose is widely applied as a sweetener in the food and pharmaceutical industries (Faustino Pereira et al, 2012;Sarrouh & Da Silva, 2010); and furfural, which has been used in oil-refining and plastics industries, is generated from xylose via dehydrocyclization (Hua et al, 2013;Petrova et al, 2010;Sun, Yang, Wang, & Zhang, 2011); Arabinose is recently reported as a lowcalorie sweetener and inhibitor of sucrase (Mikkelsen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One explanation is that the pores in the demineralized enamel surface do not allow penetration of high-concentration xylitol solutions (>20%). Pereira et al (23) showed that 10% xylitol varnish, when applied on enamel specimens, was able to promote better xylitol release in artificial saliva than 20% xylitol varnish. The authors did not test xylitol solutions.…”
Section: Discussionmentioning
confidence: 99%